THE DETERMINANTS OF BUSINESS SUCCESS IN GROCERY STORES IN SEMARANG CITY - Nabilla Zahra Alidya; Dewi Widyaningsih; Haryo Kusumo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research aims to determine the role of business capital, competitors, product diversification, financial management, and digital technology on business success. The research population is Modern Grocery Store operators in Semarang City. Data were collected through questionnaires from 50 respondents as the research sample. The research method is quantitative and data analysis uses multiple linear regression tests. From the results of the hypothesis test, there is a significant positive partial influence of the variables of business capital, competitors, product diversification, financial management and digital technology on business success. Based on the test results, the coefficient of determination is 0.971. In other words, this study model explains 97.1% of the variance in business success, while other variables explain the remaining 2.9%. Novelty: this research focuses on modern grocery stores in Semarang City, areas that have not been researched much in previous research and modern MSME-based grocery stores that adopt the concept of semi-minimarkets and adopt digital technology. Contribution: This study theoretically clarifies the role of factors in the success of MSME-based modern grocery store business and practically by providing strategic insights for grocery store owners and local policymakers to strengthen competitiveness in the modern retail sector.